PENINGKATAN KUALITAS PEMBELAJARAN BIOLOGI DENGAN METODE KOOPERATIF DI PRODI PEND. FISIKA FKIP UHN MEDAN - Surbakti, Mariana; Panjaitan, Poltak (Jurnal Visi Eksakta, 2020)
The purpose of this study was to 1) determine student learning outcomes through the Inquiry learning model on metabolic material, 2) know the learning activities of students who were taught with Inquiry learning models in Biology courses, 3) know the psychomotor attitudes of students who were taught with models cooperative learning on metabolic material. This research is an experimental research This research was conducted on physics study students at T.P. 2018/2019. The learning model used is inquiry model in the experimental class and conventional model in the control class.The results showed that: The results of the average value in the control class were: pretest = 45,517 and posttest = 61,896 The results of the average value in the experimental class are: pretest = 48.333 and post test = 80.833 Obtained data X = 80.83; S = 12.32; L hitung = 0.0937; L table = 0.161;then: L calculate <L table, then posttest data Experiment class is normally distributedFrom the results of the statistical calculation above t arithmetic = and t table = 2.003 so as to obtain the value of -2.003 <<2.003 then H0 is accepted, meaning that the initial ability of students in the experimental class is the same as the initial ability of students in the control class.From the results of the statistical calculation above t arithmetic = and t table = 1.6715 to obtain a value of t> t table ie> 1.6715 then H0 is rejected and Ha is accepted meaning there is a significant influence on the use of cooperative learning models on student learning outcomes. The coefficient of linear regression direction ( b) = 0.85 which is positive. This means that the learning outcomes of experimental class student increase due to the influence of the cooperative learning model used in the teaching and learning process in the class.